Innovation climate for individual motivation and innovation performance: Is innovative behavior a missing link? - Shan Jiang; Jun Wang; Ruilin Zhang; Ou Liu (Journal of Innovation & Knowledge (JIK), 2023)
This study empirically examines the impact of individual motivation on innovation performance, where innovative behavior serves as a mediating construct, and discusses whether the innovation climate has a moderating effect. This study combines the Cognitive Evaluation Theory and behavioral performance to develop a new theoretical method for explaining the relationships between individual motivation, innovative behavior, and innovation performance. Data collected via a field study of 250 subjects who participated in a science and technology competition were analyzed using a PLS-SEM model. Barron and Kenny's mediation test and the bootstrapping method were used to evaluate the model and confirm the mediation and moderation effects, respectively. Robustness checks were conducted to exclude nonlinearity and heterogeneity in the model. The results show that individual motivation positively promotes innovation performance, in which innovative behavior plays an intermediary role, and that innovation climate moderates the relationship between innovative behavior and innovation performance. According to the results of this field study, stimulators concerning motivation and climate should be primarily considered by managers to boost innovation performance.
Keywords: O31; O32; M00; 650; Innovation performance; Individual motivation; Innovative behavior; Innovation climate